Functional Re-organization of Cortical Networks of Senior Citizens After a 24-Week Traditional Dance Program - Zilidou, Vasiliki I.; Frantzidis, Christos A.; Romanopoulou, Evangelia D.; Paraskevopoulos, Evangelos; Douka, Styliani; Bamidis, Panagiotis D. (Frontiers in Aging Neuroscience, 2018)
Neuroscience is developing rapidly by providing a variety of modern tools for analyzing the functional interactions of the brain and detection of pathological deviations due to neurodegeneration. The present study argues that the induction of neuroplasticity of the mature human brain leads to the prevention of dementia. Promising solution seems to be the dance programs because they combine cognitive and physical activity in a pleasant way. So, we investigated whether the traditional Greek dances can improve the cognitive, physical and functional status of the elderly always aiming at promoting active and healthy aging. Forty-four (44) participants were randomly assigned equally to the training group and an active control group. The duration of the program was 6 months. Also, the participants were evaluated for their physical status and through an electroencephalographic (EEG) examination at rest (eyes-closed condition). The EEG testing was performed 1-14 days before (pre) and after (post) the training. Cortical network analysis was applied by modelling the cortex through a generic anatomical model of 20000 fixed dipoles. These were grouped into 512 cortical Regions of Interest (ROIs). High quality, artifact-free data resulting from an elaborate pre-processing pipeline were segmented into multiple, 30 seconds of continuous epochs. Then, functional connectivity among those ROIs was performed for each epoch through the Relative Wavelet Entropy (RWE). Synchronization matrices were computed and then thresholded in order to provide binary, directed cortical networks of various density ranges. The results showed that the dance training improved optimal network performance as estimated by the small-world property. Further analysis demonstrated that there were also local network changes resulting in better information flow and functional re-organization of the network nodes. These results indicate the application of the dance training as a possible non-pharmacological intervention for promoting mental and physical well-being of senior citizens. Our results were also compared with a combination of computerized cognitive and physical training, which has already been demonstrated to induce neuroplasticity (LLM Care).